Integrated miRNA-seq and functional analyses reveal the regulatory role of sha-miR-92a_L + 2R + 4 via targeting vegfaa in rainbow trout (Oncorhynchus mykiss) responding to acute hypoxia and reoxygenation stress - Yongjuan Li; Shenji Wu; Jinqiang Huang; Lu Zhao (BMC Genomics)
Abstract Background Hypoxia negatively affects the behavior, growth, reproduction and survival of fish, causing serious economic losses to aquaculture. Rainbow trout (Oncorhynchus mykiss), an important economic fish worldwide, belongs to a hypoxia-sensitive fish species, however, little is known about the regulatory mechanism of microRNAs (miRNAs) under hypoxia stress. Results Rainbow trout were subjected to hypoxia stress for 3 h (H3h_L), 12 h (H12h_L), 24 h (H24h_L) and 3 h reoxygenation (R3h_L) to systemically evaluate the changes of miRNA expression profiles in liver, and functions of sha-miR-92a_L + 2R + 4 were investigated. We found 17, 144, 57 and 55 differentially expressed (DE) miRNAs in the H3h_L vs. control (N_L), H12h_L vs. N_L, H24h_L vs. N_L and R3h_L vs. N_L comparisons, respectively. Enrichment analysis revealed that the targets of DE miRNAs were significantly enriched in HIF signaling pathway, VEGF signaling pathway, FoxO signaling pathway and glycolysis/gluconeogenesis. Through miRNA-mRNA interaction and weighted gene co-expression network analysis (WGCNA), five key DE miRNAs (sha-miR-92a_L + 2R + 4, ssa-miR-128-3p, ssa-miR-101b-3p_R + 1, ola-miR-199a-5p_R + 2 and tni-miR-199_1ss18CG) were identified, which can target at least two hypoxia-responsive genes, such as vegfaa, ho, glut1a and junb. Functional analysis found that sha-miR-92a_L + 2R + 4 directly regulated vegfaa expression by targeting its 3′-UTR, overexpression of sha-miR-92a_L + 2R + 4 significantly decreased vegfaa expression in rainbow trout liver cells, while opposite results were obtained after transfection of sha-miR-92a_L + 2R + 4 inhibitor. Furthermore, overexpressed sha-miR-92a_L + 2R + 4 promoted rainbow trout liver cell proliferation and inhibited apoptosis. Conclusion This study deepens our understanding of the crucial roles of miRNAs under hypoxia stress in rainbow trout. These results can contribute to devise strategies for improving rainbow trout survival rate and aquaculture production during hypoxia stress and help speeding up the selective breeding of hypoxia-tolerant rainbow trout.